INNOVATIVE TEACHING STRATEGIES IN BUSINESS AND ENTREPRENEURSHIP EDUCATION: A BIBLIOMETRIC ANALYSIS - Noranyza Zainol; Hariyaty Ab Wahid, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Innovative teaching strategies are vital in business and entrepreneurship education, equipping learners with the skills and mindset needed to excel in today’s dynamic environment. Despite growing demand, there is limited systematic analysis of existing literature to identify effective teaching innovations. This study addresses this gap by analyzing 726 scholarly works indexed in Scopus between 2014 and 2024. Using Scopus Analyzer and VOSviewer, the study examines co-authorship networks, keyword patterns, and citation trends to uncover key themes and collaboration networks. The analysis, visualized through network and density maps, highlights an increasing emphasis on experiential learning, developing entrepreneurial mindsets, and integrating digital tools into teaching practices. The keywords such as innovation, active learning, and entrepreneurship education frameworks dominate the discourse, reflecting their significance in the field. Citation trends also reveal influential works and prominent authors shaping the landscape of entrepreneurship education. The findings underscore the importance of interdisciplinary approaches and collaboration between academia and industry in fostering innovative teaching practices. Inconclusion, this study highlights pathways for future research and demonstrates the potential of bibliometric tools in identifying trends, fostering collaboration, and improving pedagogical strategies. By bridging research and practice, the insights contribute to building more impactful and future oriented educational frameworks in business and entrepreneurship education.